Labour and capital saving technical change in telecommunications - Madden, Gary; Bloch, Harry; Coble-Neal, Grant (Taylor & Francis, 2002)
The Australian telecommunications sector is being improved and extended throughsubstantial recent investment in intelligent technology such as digital switching, breoptics, satellite and cellular transmission, and the Internet. These technologies arebeing progressively integrated with technology from the broadcasting, computer andelectronics industries, providing a unied information infrastructure for informationtransmission and processing. Technological progress embodied in new equipment has the efect of increasing the efficiency of the factors of production. Such efficiency increases can be biased towards a particular factor. For instance, the impact oflabour-augmenting technical change is a decline in the cost of labour per unit of production. When such biases are apparent the relativity between the costs oflabour and capital per unit of production is changed. In the longer term, technical change can impact on the rate of employment growth and also on the rate of capital accumulation. In this study the Australian telecommunications cost structure is examined for the period 1919 to 1988. To measure labour saving and capital saving technical change a translog cost model is estimated. Multiproduct telecommunications cost studies typically employ the translog cost model (Evans and Heckman, 1984; Roller, 1990a; 1990b; Shin and Ying, 1992; McKenzie and Small, 1997). The translog model places no a priori restrictions on substitution possibilities among the factors of production, and allows scale economies to vary with the level of output.